Pengembangan dan Penerapan E-learning untuk Pembelajaran Efektif di Pondok Pesantren Madaarikul Ulum: Penelitian - Nurfitria Khoirunnisa; Taufan Abdurrachman; Shohib Khoiri; Lulu Latifah Nurhafsyah; Lina Sintia; Ardian Abdul Hanan; Fachry Firmansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This PKM aims to develop and implement a more effective learning ecosystem at Madaarikul Ulum Islamic Boarding School through an E-learning platform using Moodle, accompanied by digital literacy training rooted in spiritual values. Access constraints, variations in conventional teaching methods, and the need to enhance digital literacy for more than 480 students and educators drive this initiative. The methods include needs analysis, design and integration of Moodle with instructional processes, and comprehensive training for teachers and students, followed by digital literacy training that emphasizes ethics, security, and spiritual values aligned with the boarding school’s culture. Evaluation is conducted continuously through pre- and post-tests, participation observations, and participant feedback to assess improvements in technical skills, content comprehension, and the quality of learning interactions. Early results indicate enhanced technical competencies, digital literacy grounded in spiritual values, and more effective access to materials and online discussions. Moodle facilitates more structured class management and more objective assessment, supporting a learning model relevant to the boarding school. PKM could serve as a reference for other pesantrens in the effort to improve educational quality in line with SDG 4.